Developing a Structural Model of the Relationship between Cognitive Style and Emotional Creativity with the Mediating Role of Emotional-Social Competence of Adolescent Girls - Rahanjam, Homeira; Younesi, Seyyed Jalal; Shariat bagheri, MohammadMahdi (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the fit of the structural model of deterministic thinking and cognitive style and students' emotional creativity with the mediating role of creativity self-efficacy and emotional-social competence. Methods: The present research method was descriptive and the correlation research design was structural equation model. The statistical population of this study was all 11th grade female students in the second year of high school in the academic year of 2018-19 in Tehran, from which 460 people were selected by cluster random sampling. 5 districts were randomly selected from the districts of Tehran. Data were collected using the April (1999) Emotional Creativity Questionnaire, and Social Emotional Competence Questionnaire Zhu and Ji (2012) were collected. Pearson correlation coefficient and structural equation model and SPSS.22 and AMOS.22 software were used to analyze the research data. Significance level in this study was considered 0.05. Results: The results showed that the path coefficient between social emotional competency and emotional creativity (β=0.55, p